2022
DOI: 10.1177/21582440221116111
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Dots: Perceived Organization Support, Motive Fulfilment, Job Satisfaction, and Affective Commitment Among Volunteers

Abstract: In this paper, the influence of organizational factors and the role of individual factors on volunteers’ job satisfaction and affective commitment is examined, in particular, whether volunteers’ motive fulfilment mediates the influence of perceived organizational support for the two outcomes of job satisfaction and affective commitment. A crosssectional survey was used to collect data from 213 volunteers from five non-profit organizations in Queensland, Australia. Perceived organizational support is found to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Their reported result of β = 1.07, p < 0.001 implies that the positive effect of perceived organisation support on work engagement is significant. Second, the significant effect of perceived organisation support on affective commitment is evident in various studies (Ficapal-Cusi et al, 2020;Usadolo & Usadolo, 2021;Usadolo et al, 2022). For instance, a cross-sectional study in Australiaby Usadolo et al (2022) concluded that perceived organisation support significantly impacted affective commitment among participants (β = 0.39, p < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Their reported result of β = 1.07, p < 0.001 implies that the positive effect of perceived organisation support on work engagement is significant. Second, the significant effect of perceived organisation support on affective commitment is evident in various studies (Ficapal-Cusi et al, 2020;Usadolo & Usadolo, 2021;Usadolo et al, 2022). For instance, a cross-sectional study in Australiaby Usadolo et al (2022) concluded that perceived organisation support significantly impacted affective commitment among participants (β = 0.39, p < 0.001).…”
Section: Introductionmentioning
confidence: 99%